Unveiling the Forbidden: Same-sex Love as a Motif in Lydia Wahlström's Writing. Issue 4 (1st October 2016) - Borgström, Eva
Abstract: This article investigates how the historian and writer Lydia Wahlström (1869–1954) wrote about same-sex passions in a time when homosexuality was forbidden by law and tabooed in literature. There were of course also, during the first decades of the 1900s, many people who lived in same-sex relationships, some of them openly enough that this can still be discerned in the historical material. Lydia Wahlström was among them. She was active in the suffragist movement and one of its most prolific leaders, speakers, and writers. Wahlström was awarded a doctorate in history in 1898 and then became the director of studies at the Åhlinska School for girls in Stockholm. Alongside this, she wrote numerous articles and non-fiction books on a wide range of subjects as well as three romans-à-clef . In these novels, she wrote about the love that dared not speak its name, but she had to draw a veil over the forbidden motif in order to write about it. The interesting thing is that Wahlström did not mask the controversial motif more than that the observant contemporary reader could understand the underlying meaning in the novels and that it becomes even clearer to those who read her autobiography that was published many years later. This article deals with writing about same-sex love in a profoundly homophobic time.